Exhaled breath temperature increases during mild exacerbations in children with virus-induced asthma - Xepapadaki, P.; Xatziioannou, A.; Chatzicharalambous, M.; Makrinioti, H.; Papadopoulos, N. G. (Int Arch Allergy Immunol, 2010)
{Exhaled breath temperature (EBT) has been suggested as a non-invasive surrogate marker of airway inflammation in asthma. The aim of the study was to evaluate differences in EBT between periods of controlled disease and during exacerbations in children with virus-induced asthma.|Twenty-nine children (aged 6-14 years) with a history of intermittent, virus-induced asthma were included in this case-control study. Cases presented with a common cold and/or mild exacerbation of asthma, while controls were free of asthmatic or common cold symptoms during the previous 6 weeks. A baseline questionnaire was obtained. Atopy assessment, central temperature and a spirometric measurement were recorded. EBT was measured with a new device (Delmedica, Singapore). A nasal wash (for identification of common respiratory viruses) was obtained.|Twenty-four children (12 from each group) completed the study. Groups were homogeneous with respect to baseline characteristics. PCR revealed the presence of a virus in 3 out of 17 controls and 10 out of 12 cases (17.6 and 83.3%, respectively
Keywords: Adolescent Asthma Body Temperature Breath Tests Case-Control Studies Child Common Cold Cross-Sectional Studies Female Forced Expiratory Volume Humans Inflammation Male Respiratory System Rhinovirus